Consommation du pain blanc dans le milieu universitaire - BESSEGHIR, Charaf Eddine; FERNAN, Amina (My University, 2021)
Wheat is one of the most consumed cereals in Algeria, especially soft wheat (flour), whichisused in the production of several foodstuffs, the most important of whichisbread. Throughthisresearch, we have approached the stages of bread making, its components, its nutritional value and the harmthatbread can cause. To find out more about the consumption of bread, we carried out a questionnaire on 100 students at the University of Mostaganem.Several results have been found, the most important of whichisthatbreadis the foodmostconsumed by the population because of its nutritional value and itsrole in meeting theirdailynutritionalneeds. Wenoticedthatstudentseatbread (100%), majority of studentsbuy 4 loaves per day (31%) and 5 loaves per day (23%), moststudentsprefer to buybreadfrom the bakery (57 %). Studentswhoprefer to eatbread at all meals are 68%, studentswhoprefer to eat bread at noonis 19%, whilestudentswhoeatbread at dinner are 9%. 44% of students prefer white bread, 46% of studentspreferspecialtybreads and 10% prefer sandwich bread.The results obtained show that white bread is an important, necessary, useful and preferredfoodproduct for the majority of Algerian consumers (the bread is of good physicochemical and nutritional quality in the willaya of MOSTAGANEM).
Keywords: soft wheat; flour; breadmaking; white bread; physicochemicalquality; nutritional quality.